Effect of Plant Extract on Vase Life in Gerbera var. Pre Intenzz - Vinithbabu, B. V.; Preetham, S. P.; Patil, B. C.; Naveen, M. P.; Hiremath, J. S.; Kirankumar, G.; Prashantha, A. (International Journal of Economic Plants, 2025)
The present study was carried out during rabi, 2020–21 (February–June 2021) on “Effect of plant extract on vase life in gerbera” at the Department of Floriculture and Landscape Architecture, Kittur Rani Channamma College of Horticulture, Arabhavi, Bagalkot, Karnataka (591218), India. The experiments were laid out in Completely Randomized Design. Among the effect of plant extract on gerbera flowers held in vase solution containing 8-HQS @ 0.8% (Standard check) recorded the longest vase life (11.54 days), cumulative uptake of vase solution (CUV) of 31.72 g days-1, cumulative transpiration loss of vase solution (CTL) of 40.86 g days-1, minimum microbial load 2.92 cfu×10-5 which was on par with Ocimum sanctum @ 5.0% recorded the longest vase life (11.00 days), CUV of 30.82 g days-1, CTL of 39.66 g days-1, minimum microbial load 3.15 cfu×10-5. In different combinations of plant extracts the gerbera flowers held in vase solution containing T3 (Mentha viridis @ 5.0%+Ocimum sanctum @ 5.0%) had recorded a longest vase life of 9.35 days, CUV of 28.96 g days-1, CTL of 29.19 g days-1, fresh weight of 21.58 g days-1, minimum microbial load 4.04 cfu×10-5. Among the effect of plant extract on the vase life of gerbera flowers T2 (Ocimum sanctum @ 5.0%) was found to be best in maintaining vase life and its parameters and which is on par with T16 (8 HQS @ 0.8%). T3 (Mentha viridis @ 5.0%+Ocimum sanctum @ 5.0%) was found effective among the combination of plant extract.